2022
DOI: 10.1002/jbm.b.35053
|View full text |Cite
|
Sign up to set email alerts
|

Biomembrane‐mimetic hemoperfusion adsorbent for efficient removal of low‐density lipoprotein from hyperlipemia blood

Abstract: Lowering of low‐density lipoprotein (LDL) levels in blood of patients with hyperlipidaemia can effectively prevent the progression of atherosclerosis and coronary heart disease. The present study demonstrated a facile synthesis strategy to prepare biomembrane‐mimetic LDL adsorbent (PVA@COOH‐PE) via directional immobilization of phospholipid onto macro‐porous cross‐linked poly(vinyl alcohol) spheres. The binding between the prepared adsorbent and LDL particles simulates the cytosolic lipid droplets to form a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The efficacy of LDL apheresis systems is primarily determined by the adsorbents. Therefore, extensive attention has been drawn to the investigation of economical and effective adsorbents, leading to the development of various LDL ligands, such as antibodies [ 23 , 24 ], heparin [ 25 , 26 , 27 ], chondroitin sulfate [ 28 , 29 ], cyclodextrin [ 30 , 31 ], chitosan derivatives [ 32 , 33 ], phospholipid [ 34 , 35 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of LDL apheresis systems is primarily determined by the adsorbents. Therefore, extensive attention has been drawn to the investigation of economical and effective adsorbents, leading to the development of various LDL ligands, such as antibodies [ 23 , 24 ], heparin [ 25 , 26 , 27 ], chondroitin sulfate [ 28 , 29 ], cyclodextrin [ 30 , 31 ], chitosan derivatives [ 32 , 33 ], phospholipid [ 34 , 35 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its adsorption capacity for HDL was significantly lower at only ∼0.77 mg/g, underscoring its selective binding performance for LDL and resistance to atheroprotective HDL. Importantly, the adsorption performance of Fe 3 O 4 @SiO 2 @Azo-COOH surpassed that of previously reported adsorbents [ 15 , 22 , 45 , 46 ]. Additionally, Fe 3 O 4 @SiO 2 @Azo-COOH displayed excellent adsorption–desorption behaviour for LDL, TG and TCH due to its photocontrolled irradiation capabilities, thereby reducing synthesis costs and resource wastage.…”
Section: Discussionmentioning
confidence: 51%
“…acute coronary syndrome [ 10 ], muscle weakness [ 11 ], muscle pain [ 12 ] and low efficacy) from existing treatments and inefficacy in managing patients with LDL levels above 300 mg/dl [ 13 ] pose significant obstacles to HLP treatment. Studies have indicated that selectively lowering LDL level while maintaining HDL with anti-atherosclerotic properties in patients represents a promising clinical treatment strategy for HLP [ 14 , 15 ]. Encouragingly, hemopurification-based adsorption has shown to be an effective therapy for treating HLP, demonstrating not only good adsorption efficiency for pathogenic LDL and selectivity adsorption resisting HDL, but also a reduction in toxicities, particularly effective for patients with familial hypercholesterolemia [ 16 ] and those who fail to achieve complete recovery through diet and drug therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, six prevalent LDL apheresis technologies are accessible, with four relying on the adsorption principle—dextran sulfate adsorption, dextran sulfate direct perfusion, polyacrylate-coated polyacrylamide direct perfusion and immune-adsorption [ 16 , 17 , 18 ]—which underscores the pivotal role of the adsorption material as a determining factor in the therapeutic efficacy of LDL-apheresis systems. Consequently, considerable focus has been directed towards exploring cost-effective and efficient adsorbents, resulting in the emergence of diverse LDL ligands, including antibodies [ 19 , 20 ], heparin [ 21 , 22 , 23 , 24 ], chondroitin sulfate [ 25 , 26 ], amino acid [ 27 ], phospholipids [ 28 , 29 ], chitosan derivatives [ 30 , 31 ] and others. Typically, a predominant feature of low-density lipoprotein (LDL) adsorption materials involves the incorporation of anionic characteristics.…”
Section: Introductionmentioning
confidence: 99%